Meningkatkan Keterampilan Gerak Kata “Empi” Dengan Latihan Imagery Karateka Lemkari Banjarmasin - Baidillah, Baidillah; Mashud, Mashud; Arifin, Syamsul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the improvement of kata empi movement skills through imagery training at Karateka Lemkari Banjarmasin (PTO). This research uses a sports action research method with a cycle of planning, implementation, observation, and reflection. The research subjects were 26 Lemkari Banjarmasin karateka in the age range of 5-20 years with training experience of 1-10 years. The instrument in this research was a kata movement sequence test based on the WKF Kata and Kumite Competition Rules Revision 9.0 kata assessment criteria. 3 main assessments carry equal weight, namely conformity to the original form and applicable standards, technical performance, and athletic performance. Each assessment has a value weight of 1/3. The weight is assessed by scoring if the karateka displays movements according to the indicators. Analysis of assessment data for each cycle in sports action research uses quantitative and qualitative techniques. The results showed increased movement skills for the word